Cortisol responses to mental stress and the progression of coronary artery calcification in healthy men and women. - Mark Hamer; Romano Endrighi; Shreenidhi M Venuraju; Avijit Lahiri; Andrew Steptoe (PLoS ONE)
Background Psychosocial stress is a risk factor for coronary heart disease (CHD). The mechanisms are incompletely understood, although dysfunction of the hypothalamic pituitary adrenal (HPA) axis might be involved. We examined the association between cortisol responses to laboratory-induced mental stress and the progression of coronary artery calcification (CAC). Methods and results Participants were 466 healthy men and women (mean age = 62.7±5.6 yrs), without history or objective signs of CHD, drawn from the Whitehall II epidemiological cohort. At the baseline assessment salivary cortisol was measured in response to mental stressors, consisting of a 5-min Stroop task and a 5-min mirror tracing task. CAC was measured at baseline and at 3 years follow up using electron beam computed tomography. CAC progression was defined as an increase >10 Agatston units between baseline and follow up. 38.2% of the sample demonstrated CAC progression over the 3 years follow up. There was considerable variation in the cortisol stress response, with approximately 40% of the sample responding to the stress tasks with an increase in cortisol of at least 1 mmol/l. There was an association between cortisol stress reactivity (per SD) and CAC progression (odds ratio = 1.27, 95% CI, 1.02-1.60) after adjustments for age, sex, pre-stress cortisol, employment grade, smoking, resting systolic BP, fibrinogen, body mass index, and use of statins. There was no association between systolic blood pressure reactivity and CAC progression (odds ratio per SD increase = 1.03, 95% CI, 0.85-1.24). Other independent predictors of CAC progression included age, male sex, smoking, resting systolic blood pressure, and fibrinogen. Conclusion Results demonstrate an association between heightened cortisol reactivity to stress and CAC progression. These data support the notion that cortisol reactivity, an index of HPA function, is one of the possible mechanisms through which psychosocial stress may influence the risk of CHD.